Reactive Hyperplasias in the Oral Mucosa: Case Series - Nuray Bağcı; İlkay Peker; Özlem Üçok (Ankara University, 2022)
Aim: Reactive hyperplasias are often encountered tumor-like exophytic lesions of the oral mucosa, but they are not a neoplasm. Local factors such as dental calculus, food residue stuck between teeth, incompatible prosthetic restoration, and systemic factors such as hormonal changes play a role in the etiology of these hyperplasia. The aim of this presentation is to evaluate the possible etiological factors, clinical, and radiological findings of 10 reactive hyperplasia cases seen in different regions of the mouth. Case report: Ten patients (seven females and three males) with a mean age 40.2 applied to our clinic with complaints of swelling in the mouth. In the medical anamnesis, it was learned that three (30%) patients had recently given birth and the related swelling started to occur in the second trimester of pregnancy, three (30%) patients had different diseases such as heart, hypertension, diabetes, and cholesterol, and were under regular medication for systemic disease. There is no finding on extraoral examination. In intraoral examination, mass lesions which red and/or pink, lobular/nodular, painless, pedunculated and/or sessile, and smooth and/or ulcerated was seen on the maxilla of six patients, mandible of three patients, and lower lip mucosa of one patient. Poor oral hygiene in seven (70%) patients, prosthetic restoration in the lesion-related area in two (20%) patients, and attrition incisal tooth surface and diastema in one (10%) patient were found. Radiographic examination revealed that minimal resorption on the alveolar crest in the lesion-related area of only three (30%) patients was seen. All lesions were histopathologically examined after surgical excision. According to the clinic, radiographic and histopathological features, diagnosis of the lesions was made as pyogenic granuloma (four cases; 40%), peripheral ossifying fibroma (three cases; 30%), traumatic fibroma (two cases; 20%) and peripheral giant cell granuloma (one case; 10%). Conclusion: It was concluded that the lesions examined in this case series were mostly caused by local factors. The clinical findings observed in the patients were red nodular mass, painless, soft, and smooth-surfaced. In the radiographic examination, no finding was detected in most of the lesions.